2013
DOI: 10.1161/atvbaha.112.300717
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Coronary Arterial Course Is Associated With Coronary Arterial Stenosis and Prognosis of Major Cardiac Events

Abstract: Objective-The clinical significance of an intramural course (or bridging) of the coronary artery remains controversial. We investigated the relationship between intramural coronary arteries (ICAs) and coronary stenosis and prognosis of subjects with ICA. Methods and Results-ICA and coronary stenosis were assessed by multidetector computed tomography coronary angiography. ICAs in the left anterior descending artery were studied, which were further classified as superficial (≤2 mm) or deep type (>2 mm). Coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…The most likely explanation for their fi nding was that deep MB has hemodynamic signifi cance causing a disturbed fl ow in the other coronary arteries leading to atherosclerotic changes. 14 In our study, there was no signifi cant association between PFV with MB length, depth and proximal stenosis presence and higher PFV was observed in patients with LADA MB.…”
Section: Discussioncontrasting
confidence: 61%
“…The most likely explanation for their fi nding was that deep MB has hemodynamic signifi cance causing a disturbed fl ow in the other coronary arteries leading to atherosclerotic changes. 14 In our study, there was no signifi cant association between PFV with MB length, depth and proximal stenosis presence and higher PFV was observed in patients with LADA MB.…”
Section: Discussioncontrasting
confidence: 61%
“…The association of MB with cardiovascular risk and the possible cardiovascular risk factors remain unclear [2,3,[12][13][14][15][16][17][18]. Therefore, this study aimed to examine the clinical characteristics and related factors of coronary stenosis proximal to an MB.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the MB is not associated with the risk of cardiovascular (CV) death or myocardial infarction (MI) [10], but this finding remains controversial [11]. Studies suggested that the MB shifts the local hemodynamics toward an increased CV risk [2,12,13], while other reports indicated that individuals with or without an MB have similar CV risk [3,[14][15][16][17][18]. Nevertheless, irrespective of the CV risk, it is well recognized that the LAD under an MB or distal to the MB remains free of atherosclerosis, while the proximal part of the MB is vulnerable to the development of atherosclerotic plaques and stenosis [2, 4, 12-14, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that MB (both superficial and deep) is associated with non-significant stenosis proximal to the bridged area and that MB in middle LAD is positively associated with stenosis in non-bridged arteries. The most likely explanation for the latter is the fact that deep MB has hemodynamic significance, causing a disturbed flow in the other coronaries, and therefore increases the frequency of atherosclerotic deposits 57 . By compressing the tunnelled artery during systole, MB increases lymph drainage of the vessel wall, protecting against lipid accumulation within the bridged coronary wall 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%